KAJIAN POTENSI DAN PELUANG EKSPOR ROTAN INDONESIA (Study on the potential and opportunity of Indonesian rattan export) - Kirsfianti L Hariwibowo (Jurnal Penelitian Hasil Hutan, 1990)
The purpose of  this Study  18  to obtain information concerning the Indonaian  rattan market share  and analyze a .trategy needed  for developing market in effort to increase lndonaian  share  in world market.The analysis  reveal that current lndonaian  market hare iB mil.relatively low (<  19'); and the billlat  ah.are  iB on the commodity group which hOB tlte loweat market pofential t.e. inatti111/lampitof rattan. In (act other commodi~  group uch aa iattan furniture, and baketry  have a wider market to panetrate. The availability of raw material, as suaeeted by thiB lhuly  convinca  the poaibility  of  eJOf)anding  the rattan  indudrie&       .7b  develop lndoneSian market hare, however, the following factors are needed to emphasize :    (1) e:Kport priority ahould be foc.,;..d on to •the  llighut   co111uming country, (2) the quality of product. should be improved and (3) in the lorwer term. to broaden international market network.